ABU RAYXAN BERUNIY HÁM HÁZIRGI ZAMAN MATEMATIKASÍ - Prenov, B.; Oteniyazov, E. (SCIENCE and SOCIETY, 2023)
The article is dedicated to the 1050th anniversary of the famous Central Asian scientist Abu Rayhan Beruni and his scientific activities in mathematics.